Bilateral traumatic C6-C7 facet dislocation with C6 spondyloptosis and large disk sequestration in a neurologically intact patient. (July 2020) - Haimovich, Liad; Uri, Ofir; Bickels, Jacob; Laufer, Gil; Gutman, Gabriel; Folman, Yoram; Behrbalk, Eyal
Traumatic cervical spondyloptosis is an uncommon and severe form of facet joint dislocation that commonly leads to severe neurological damage. Decision making regarding the reduction and fixation technique is challenging, especially when a patient is neurologically intact, since an undiagnosed prolapsed disk at the involved level may lead to severe neurological consequences during reduction. A 24-year-old male was admitted after sustaining a severe direct axial blow to his head. Computed tomographic and magnetic resonance imaging scans revealed an acute C6C7 fracture dislocation with spondyloptosis of C6 vertebra and a large disk fragment posterior to C6 vertebral body. The patient was neurologically intact, apart from mild bilateral numbness over C6 distribution. The patient underwent C6 corpectomy to avoid acute cord compression related to the large sequestered disk behind C6 vertebra. Following C6 corpectomy, we were unable to exert enough axial pull to reduce the facet dislocation through the anterior approach. Therefore, the reduction was performed through a posterior approach with C5T1 posterior fusion, followed by anterior cage placement and C5-7 anterior fusion (front-back-front approach). At postoperative follow-up of 24 months, the patient demonstrated a full and pain-free cervical range-of-motion and remained neurologically intact. Follow-up radiographs of the cervical spine demonstrated good instrumental alignment with solid fusion at 6-month follow-up.